2020
DOI: 10.1093/ntr/ntaa221
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Vaping Products When Underage: A Qualitative Study of Young Adults in Southern California

Abstract: Introduction California implemented multiple strategies, such as a Tobacco 21 law and compliance checks, to reduce high rates of youth e-cigarette use. However, the prevalence of use among underage youth and young adults continues rising. Little is known about how underage individuals obtain e-cigarettes. Methods We conducted structured qualitative interviews with 61 young adult (18-25 years old) vapers in the Los Angeles, CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Previous studies have shown that students often access vaping products such as e-cigarettes for the first time in school. 42 , 43 Students have also reported that borrowing and selling products to other classmates were very common. 41 Policies, programs, and educational campaigns which denormalize e-cigarette use and make e-cigarettes more difficult for high school students to access are needed to decrease high school e-cigarette use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that students often access vaping products such as e-cigarettes for the first time in school. 42 , 43 Students have also reported that borrowing and selling products to other classmates were very common. 41 Policies, programs, and educational campaigns which denormalize e-cigarette use and make e-cigarettes more difficult for high school students to access are needed to decrease high school e-cigarette use.…”
Section: Discussionmentioning
confidence: 99%
“…In response to these concerning youth flavoured vaping trends, the FDA has sought to ban the sale of flavoured ENDS products without premarket approval and has made it an enforcement priority to seek out those who may be violating this ban 10. However, comprehensively addressing the unique challenges of online outlets that enable ENDS marketing, sales and access requires more comprehensive surveillance, regulation and enforcement at the local, state, Federal and digital platform level.…”
Section: Discussionmentioning
confidence: 99%
“…Online purchasing of ENDS represents its own unique risk environment, particularly for youth and adolescents due to lack of sufficient regulation. For example, findings from qualitative interviews with young adults have found that ENDS online sales rarely involved age verification 10…”
Section: Introductionmentioning
confidence: 99%
“…The analytic sample included 62 participants, which have been described previously [17]; see Table 1. Briefly, the sample was majority male, racially and ethnically diverse, about 21 years of age at the time of the survey, and living within comfortable financial means.…”
Section: Participant Characteristicsmentioning
confidence: 99%